Perempuan Karir Dalam Menjaga Ketahanan Keluarga (Studi Kasus Tenaga Medis Klinik Kasih Ibu Kabupaten Jember) - Hardandy, Ammalia Nur Medina Putri; Hidayah, Lailul; Nurhayati, Alfisyah; Arif , Muhamad Ridwan (CV. ITTC INDONESIA, 2024)
As time goes by, women no longer take care of the household but choose to enter the world of work to have a career. As well as career women who work as health workers whose work system uses a shift work system and must always be ready to provide services to anyone who needs it, anytime and anywhere. The data collection used in this study uses observation, interviews. This research aims to find out how the division of roles in the household and also about how to build family resilience for career women.. The result of this study is that good communication is essential to prevent miscommunication. In the family, we must also help each other, help each other in housework, educate children. That way, family resilience will be formed so that a quality family is realized.